Formation of Sub-Permafrost Methane Hydrate Reproduced by Numerical Modeling - Li, Zhen (Dr.) (2023)
Natural gas hydrates are ice-like crystalline compounds containing water cavities that trap natural gas molecules like methane (CH4), which is a potent greenhouse gas with high energy density. The Mallik site at the Mackenzie Delta in the Canadian Arctic contains a large volume of technically recoverable CH4 hydrate beneath the base of the permafrost. Understanding how the sub-permafrost hydrate is distributed can aid in searching for the ideal locations for deploying CH4 production wells to develop the hydrate as a cleaner alternative to crude oil or coal. Globally, atmospheric warming driving permafrost thaw results in sub-permafrost hydrate dissociation, releasing CH4 into the atmosphere to intensify global warming. It is therefore crucial to evaluate the potential risk of hydrate dissociation due to permafrost degradation. To quantitatively predict hydrate distribution and volume in complex sub-permafrost environments, a numerical framework was developed to simulate sub-permafrost hydrate formation by coupling the equilibrium CH4-hydrate formation approach with a fluid flow and transport simulator (TRANSPORTSE). In addition, integrating the equations of state describing ice melting and forming with TRANSPORTSE enabled this framework to simulate the permafrost evolution during the sub-permafrost hydrate formation. A modified sub-permafrost hydrate formation mechanism for the Mallik site is presented in this study. According to this mechanism, the CH4-rich fluids have been vertically transported since the Late Pleistocene from deep overpressurized zones via geologic fault networks to form the observed hydrate deposits in the Kugmallit–Mackenzie Bay Sequences. The established numerical framework was verified by a benchmark of hydrate formation via dissolved methane. Model calibration was performed based on laboratory data measured during a multi-stage hydrate formation experiment undertaken in the LArge scale Reservoir Simulator (LARS). As the temporal and spatial evolution of simulated and observed hydrate ...